The Indonesian Postal Service as an Instrument of Social Inclusion: A Case Study of Social Assistance Distribution through Kantor Pos Indonesia (Universitas Terbuka, 2025)
This study examines the strategic role of the Indonesian Post Office (Kantor Pos Indonesia) as an instrument of social inclusion within the country’s social protection framework. Employing a descriptive qualitative approach, data were collected through in-depth interviews, document analysis and field observations in selected locations representing diverse regional characteristics of Indonesia. The findings reveal that the Indonesian Post Office plays an irreplaceable role in connecting government social protection programs with marginalized populations, particularly those in remote and unbankable communities. Its nationwide network enables the distribution of various cash and non-cash assistance programs such as BST, BLT, BPNT and PKH, with a high level of timeliness, accuracy and beneficiary coverage. Moreover, the integration of digital technologies barcode systems, Pos Giro Mobile (PGM) / Pos Giro Cash (PGC), real-time tracking and NIK-based verification has substantially enhanced transparency, efficiency and accountability in service delivery. The study concludes that the Indonesian Post Office functions not merely as a logistical institution but as a social infrastructure that embodies the state’s commitment to justice, inclusivity and equitable access to public services. Strengthening infrastructure, human resource capacity and inter-sectoral coordination is recommended to sustain its contribution to SDG 1 (No Poverty) and SDG 10 (Reduced Inequalities) within Indonesia’s social welfare system.